2018
DOI: 10.17138/tgft(5)15-25
|View full text |Cite
|
Sign up to set email alerts
|

Soil attributes of a silvopastoral system in Pernambuco Forest Zone

Abstract: This research evaluated soil properties in a silvopastoral system using double rows of tree legumes. Treatments were signalgrass (Brachiaria decumbens) in monoculture or in consortium with sabiá (Mimosa caesalpiniifolia) or gliricidia (Gliricidia sepium). Treatments were arranged in a complete randomized block design, with 4 replications. Response variables included chemical characteristics and physical attributes of the soil. Silvopastoral systems had greater (P<0.001) soil exchangeable Ca (gliricidia = 3.2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In addition, du Toit et al (2009) concluded that high stocking rates not only reduced water infiltration rate in the soil but also affected soil bulk density in an area dominated by mixed vegetation of grasses and shrubs in South Africa. Therefore, in many cases animal trampling is considered one of the main causes of the negative trends on soil water infiltration in pasture (Lima et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, du Toit et al (2009) concluded that high stocking rates not only reduced water infiltration rate in the soil but also affected soil bulk density in an area dominated by mixed vegetation of grasses and shrubs in South Africa. Therefore, in many cases animal trampling is considered one of the main causes of the negative trends on soil water infiltration in pasture (Lima et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in bulk density, soil porosity, soil compaction, water infiltration rate, organic C and aggregate stability, and root resistance to soil penetration in soil (Kurz et al, 2006; Ibáñez et al, 2007; Bell et al, 2011; Lima et al, 2018) interfere with root growth and development. Nitrogen fertilization is another factor that can modify plant growth, promoting greater biomass production and nutrient assimilation (Lee et al, 2017), besides increasing C storage in the soil (Silveira et al, 2013; da Silva et al, 2015).…”
mentioning
confidence: 99%
“…Nutrient deficits -mainly, nitrogen and phosphorus -are considered as the main causes of pasture decline (BODDEY et al, 2004). To maintain sustainable animal production, fertilizers are required, but alternatively nitrogen can be supplied by tree, shrub or forage legumes (MUIR et al, 2014;LIMA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The difference in the simulation accuracy among the zones suggests that different soil parameters should be used for zones closer to the trees. The tree roots have the potential to accelerate the rate of soil water infiltration (Lima et al, 2018), also the evapotranspiration near the trees is potentially higher than the zones farther from the tree trunk . On top of that, during the dry season, the soil water content may become relatively lower near the trees (Crestani et al, 2017).…”
Section: Soil Water Simulationmentioning
confidence: 99%